Psychometrics of the continuous mind: Measuring cognitive sub-processes via mouse tracking. - Scherbaum, Stefan; Dshemuchadse, Maja (Memory & Cognition, 2020)
The measurement of psychological properties often relies on discrete measures, for example, answers in questionnaires or responses in tasks. This focus on discrete measures neglects information that is present in the process leading to an answer or a response. A method to trace such processes is mouse tracking. Mouse tracking promises to open a continuous window onto the processes leading from a stimulus to a response. However, most mouse-tracking studies fall short of the promise to extract dynamic psychometrically valid markers for the different sub-processes, which are intertwined on the way to the final response. Here we used time-continuous multiple regression (TCMR) to extract dynamic markers for the different sub-processes leading to a response. From these markers, we extracted information about the timing, the duration, and the strength of the influence of the different sub-processes. We evaluated these dynamic measures of sub-processes for their psychometric properties, i.e. reliability, which is a basis for their use in the study of individual differences. Furthermore, we applied these dynamic measures in a group-level study to identify differences in the sub-processes of resolving response conflict between groups performing either a Simon or a flanker task. We found specific temporal patterns that match predictions from a conceptual model of these tasks. We concluded that the extracted information from mouse movements could be used as psychometrically valid dynamic measures of psychological properties and their differences across individuals and situations. A software toolbox to perform the described analyses in Matlab is provided (osf.io/5e3vn).